Improving the capabilities of NHS organisations to use evidence: a qualitative study of redesign projects in Clinical Commissioning Groups - Jacqueline Swan; Emmanouil Gkeredakis; Rachel M Manning; Davide Nicolini; David Sharp; John Powell (National Institute for Health Research, 2017)
Background: Innovation driven by authoritative evidence is critical to the survival of England's NHS. Clinical Commissioning Groups (CCGs) are central in NHS efforts to do more with less. Although decisions should be based on the 'best available evidence', this is often problematic, with frequent mismatches between the evidence 'pushed' by producers and that used in management work. Our concern, then, is to understand practices and conditions (which we term 'capabilities') that enable evidence use in commissioning work. We consider how research gets into CCGs ('push'), how CCGs use evidence ('pull') and how this can be supported (toolkit development). We aim to contribute to evidence-based NHS innovation, and, more generally, to improved health-care service provision. Method: Supported by the National Institute for Health Research (NIHR), we conducted semistructured ethnographic interviews in eight CCGs. We also conducted observations of redesign meetings in two of the CCGs. We used inductive and deductive coding to identify evidence used and capabilities for use from the qualitative data. We then compared across cases to understand variations in outcomes as a function of capabilities. To help improvements in commissioning, we collated our findings into a toolkit for use by stakeholders. We also conducted a small-scale case study of the production of evidence-based guidance to understand evidence 'push'. Results: Fieldwork indicated that different evidences inform CCG decision-making, which we categorise as 'universal', 'local', 'expertise-based' and 'trans-local'. Fieldwork also indicated that certain practices and conditions ('capabilities') enable evidence use, including 'sourcing and evaluating evidence', 'engaging experts', 'effective framing', 'managing roles and expectations' and 'managing expert collaboration'. Importantly, cases in which fewer capabilities were recorded tended to report more problems, relative to cases in which needed capabilities were applied. These latter cases were more likely to effectively use evidence, achieve objectives and maintain stakeholder satisfaction. We also found that various understandings of end-users are inscribed into products by evidence producers, which seems to reflect the evolving landscape of the production of authoritative evidence. Conclusions: This was exploratory research on evidence use capabilities in commissioning decisions. The findings suggest that commissioning stakeholders need support to identify, understand and apply evidence. Support to develop capabilities for evidence may be one means of ensuring effective, evidence-based innovations in commissioning. Our work with evidence producers also shows variation in their perceptions of end users, which may inform the 'push'/'pull' gap between research and practice. There were also some limitations to our project, including a smaller than expected sample size and a time frame that did not allow us to capture full redesign projects in all CCGs. Future work: With these findings in mind, future work may look more closely at how information comes to be treated as evidence and at the relationships of capabilities to project outcomes. Going forward, knowledge, especially that related to generalisability, may be built by means of a longer time and the study of redesign projects in different settings. Funding: The NIHR Health Services and Delivery Research programme.